(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the proportion of proper dengue fever prevention practices and related factors among mothers with children under 15 years of age in Vi Thanh city, Hau Giang province in 2024. Method: A cross-sectional study was conducted from April 2024 to October 2024 among 400 mothers with children under 15 residing in Vi Thanh city, Hau Giang province, using structured questionnaires and observational checklists. Results: The proportion of mothers with good dengue fever prevention practices was 81.5%; most mothers (90.7%) reported performing larvae elimination measures and checking water containers weekly, with covering water containers being the most common method (31.5%). When suspecting illness, 74.2% chose to seek care at health facilities. Conclusion: The dengue prevention practices of mothers in Vi Thanh are generally quite good overall, but limitations remain in the application of some specific control measures and the mothers’ initial management approach for their children.